TONALITE-THRONDEMITE-GRANODIORITE (TTG) ASSOCIATIONS OF THE MIDDLE DNIEPER ARCHEAN CRATON - Sukach, V.; Kurylo, S.; Grinchenko, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Plagiogranites comprize about 70% of whole area the Middle Dnieper craton (MDC) which is allocated within the megablock of the Ukrainian Shield (USh) of the same name. They form dome or swell-like structures situated between the set of of greenstone belts (structures) of synclinal morphology. Some authors treat these plagiogranite as typical formations of tonalite-trondhemite-granodiorite (ТТG) associations/series though such term did not receive wide usage among ukrainian researchers. The aim of this publication is the determination of amount and general features of TTG of associations in MDC and their comparative analysis with similar Archean formations of known cratons of the world. On their composition, archean plagiogranites of MDC are generally similar to TTG associations of the world. We relate plagiogranites of Dnepropetrovsk, Saksagan and Sura complexes to the TTG associations of Middle Dnieper area. Among the exceptions are hypabissal and volcanogenic rocks which comprize small massifs, subvolcanic bodies and dikes within of greenstone structures; differently migmatized supracrustal rocks of both basic and average to felsic compositions; microclime-rich varieties of plagiogranites; bifeldspar granitoids which commonly occur among plagiogranites with subtle and gradual transitions to them. Probable affinity between plagiogranites of Dnepropetrovsk, Saksagan and Sura complexes is proved by bulk chemical and mineral composition, patterns and distribution of admixture-elements and petrographic features. Possible affinity between plagiogranites of Dnepropetrovsk, Saksagan and Sura complexes is proved by total chemical and mineral composition, distribution patterns of admixture-elements and petrographic features. By making review of published data available there is possibity to draw a conclusion, that plagiogranites are formed within the age interval of 3,1-2,9 bln years. Certain periods of activization are allocated which age limints are not still finally established. Though somewhere they show specific features of their composition and areal distribution. The problem of identification and mapping of plagiogranite ТТG associations of MDC requires their more comprehensive and complex substantiation with using both traditional and current precise analytycal methods.